2018
DOI: 10.3390/vetsci5040097
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Kuribayashi, T. et al. Seroprevalence of Immunoglobulin E Antibodies against Japanese Cedar Pollen Allergens Cry j1 and Cry j2 in Dogs Bred in Japan. Vet. Sci. 2018, 5, 79

Abstract: Due to an error during production, the column title of Figure 2 and Figure 3 are misaligned in the Results section of the published paper [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…In the first phase of study, prevalence of CAD from visiting dogs was 1.16 percent and percentage of CAD dogs from skin disease's dogs and allergic dermatitis's dogs were 11.61% and 40.48% respectively. The results were lower than previous reports (Hillier and Griffin, 2001;Hill et al, 2006;Kuribayashi et al, 2018).…”
Section: Phase 2: Distribution Of Causative Allergenscontrasting
confidence: 91%
See 2 more Smart Citations
“…In the first phase of study, prevalence of CAD from visiting dogs was 1.16 percent and percentage of CAD dogs from skin disease's dogs and allergic dermatitis's dogs were 11.61% and 40.48% respectively. The results were lower than previous reports (Hillier and Griffin, 2001;Hill et al, 2006;Kuribayashi et al, 2018).…”
Section: Phase 2: Distribution Of Causative Allergenscontrasting
confidence: 91%
“…Atopic dogs accounted for 40% of dermatological problem dogs in the United Kingdom ). Kuribayashi's study reported that canine atopic dermatitis accounted for 50% of skin disease's dog in Japan (Kuribayashi et al, 2018). However, based on the results of intradermal skin testing, there is only one report on the prevalence of canine atopic dermatitis in Thailand (Chanthick et al, 2008).…”
Section: Importance and Rationalementioning
confidence: 99%
See 1 more Smart Citation